Protocol for intraoperative assessment of the human cerebrovascular glycocalyx - Haeren, R H L (BMJ Open, 2017)
INTRODUCTION: Adequate functioning of the blood–brain barrier (BBB) is important for brain homoeostasis and normal neuronal function. Disruption of the BBB has been described in several neurological diseases. Recent reports suggest that an increased permeability of the BBB also contributes to increased seizure susceptibility in patients with epilepsy. The endothelial glycocalyx is coating the luminal side of the endothelium and can be considered as the first barrier of the BBB. We hypothesise that an altered glycocalyx thickness plays a role in the aetiology of temporal lobe epilepsy (TLE), the most common type of epilepsy. Here, we propose a protocol that allows intraoperative assessment of the cerebrovascular glycocalyx thickness in patients with TLE and assess whether its thickness is decreased in patients with TLE when compared with controls. METHODS AND ANALYSIS: This protocol is designed as a prospective observational case–control study in patients who undergo resective brain surgery as treatment for TLE. Control subjects are patients without a history of epileptic seizures, who undergo a craniotomy or burr hole surgery for other indications. Intraoperative glycocalyx thickness measurements of sublingual, cortical and hippocampal microcirculation are performed by video microscopy using sidestream dark-field imaging. Demographic details, seizure characteristics, epilepsy risk factors, intraoperative haemodynamic parameters and histopathological evaluation are additionally recorded. ETHICS AND DISSEMINATION: This protocol has been ethically approved by the local medical ethical committee (ID: NL51594.068.14) and complies with the Declaration of Helsinki and principles of Good Clinical Practice. Informed consent is obtained before study enrolment and only coded data will be stored in a secured database, enabling an audit trail. Results will be submitted to international peer-reviewed journals and presented at international conferences. TRIAL REGISTRATION NUMBER: NTR5568.